2020
DOI: 10.1002/jhet.3990
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene derivatives: A potent multitargeted pharmacological scaffold

Abstract: Despite a significant work that has been done on thiophene, continuous efforts are still being made by the researchers to identify novel heterocyclic compounds with potential bioactivities. Thiophene nucleus has been extensively utilized by the researchers across the globe for the development of diverse bioactive heterocycles for hitting a wide range of biological targets. This review throws light on synthetic approaches that have been used for the synthesis of potential thiophene derivatives followed by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…5. The Kb values of compounds (3a-d) are found to be 1.1216X10 7 , 1.4072X10 7 , 1.0634X10 7 and 3.4872X10 7 respectively appear in Table 6. These Kb values conforms all the synthesized compounds interacted strongly with CT-DNA.…”
Section: Cytotoxicity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…5. The Kb values of compounds (3a-d) are found to be 1.1216X10 7 , 1.4072X10 7 , 1.0634X10 7 and 3.4872X10 7 respectively appear in Table 6. These Kb values conforms all the synthesized compounds interacted strongly with CT-DNA.…”
Section: Cytotoxicity Studymentioning
confidence: 99%
“…Current chemotherapies suffers major limitation of side effect and drug resistance, therefore continued search for novel and safer anticancer drugs remains as important [5]. Pyrimidine and thiophene have been recognized as key scaffolds due to its biological significances such as antiviral, antibacterial, antifungal, anticancer, antiinflammatory, anti-diabetic, anti-tubercular, antioxidant, anti-parasitic, anti-convulsants, antidepressant, analgesic, antitumor, gastro protectors and kinase inhibitors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Substituted thiophenes have been utilized as key structural units in significant bioactive pharmacophores, [1,2] and also as important building blocks in organic and medicinal chemistry. [3][4][5] Several thiophene-based compounds have been synthesized to screen their biological activities such as antimicrobial, [6][7][8] cytotoxic, [9,10] antiinflammatory, [11] anti-arrhythmic, [12] and antidepressant [13] agents. Many thiophene derivatives like ISO-930, Raloxifene, and Raltitrexed (Figure 1) have been marketed as anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that the solubility of active pharmaceutical ingredients can be increased by the preparation of nanoparticles and by optimization of physicochemical properties [9,10,11]. Besides, indole and thiophene derivatives have wide range of pharmacological activity including anticancer, antimicrobial and antiinflammatory [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%